Durability Evaluation of Reinforced Glass-Flake Polyester Material Used in Rehabilitation of Sewer Lines in Buildings -Dataset - Kharazmi, Parastou (Royal Institute of Technology, 2019)
This dataset includes original data to support parts of research findings stated in the article: ”Durability evaluation of reinforced glass-flake polyester material used in rehabilitation of sewer lines in buildings”. Currently, different materials and methods are in use in alternative rehabilitations technologies for sewer renewal. This work was conducted to study one of these materials, which is a glass -flake reinforced polyester polymeric system, during artificial aging to provide a better understanding of the material’s performance under operating conditions when it is regularly exposed to degrading factors such as high temperature and water. Changes in the material during aging were monitored by conducting different tests, including thermal and mechanical analysis, water absorption and microscopy.

The dataset was originally published in DiVA and moved to SND in 2024.

Denna datauppsättning innehåller originaldata för att stödja delar av forskningsresultaten som anges i artikeln: ”Durability evaluation of armed glass-flake polyester material used in rehabilitation of sewer lines in buildings”.

Se engelsk beskrivning för mer information.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Durability Evaluation of Reinforced Glass-Flake Polyester Material Used in Rehabilitation of Sewer Lines in Buildings -Dataset
Keywords: Waste-Water Sewer; Waste-Water Sewer; Aging; Aging; Polyester; Polyester; Relining Materials; Relining Materials; Rehabilitation; Rehabilitation; Building Technologies; Husbyggnad; Water Engineering; Vattenteknik; Surface- and Corrosion Engineering; Yt- och korrosionsteknik; Composite Science and Engineering; Kompositmaterial och kompositteknik; Other Environmental Engineering; Annan naturresursteknik